Mencairnya Identitas Mahasiswa Melalui Second Account di Instagram - Fioreza Fahira Zahra; Rakhmat Hidayat; afdhal Afdhal (The Journal of Society and Media, 2022)
This study discusses the phenomenon of the melting of the identities of eight UNJ students in Instagram. This study uses a qualitative approach. Data were collected through in-depth interviews, observation, documentation, and literature review methods. Previous research has shown that Instagram as a social media is able to construct a new identity through exploration and sharing of its self. This study provides evidence that a new self-identity can be constructed in Instagram through a second account. Here different identities are shown to the audience with different characteristics. The ideal identity construction is displayed on First Account according to their persona. The continuous use of two accounts has various implications, such as identity fragmentation, being trained to provide a different identity appearance, freedom of expression in cyberspace and being open with digital society, and experiencing identity exploration that leads to self-discovery and development.